HOW CUP POSITION AFFECTS DISLOCATION RATE IN PROXIMAL FEMORAL REPLACEMENT ARTHROPLASTY - Khattak, Sabir Khan; Nauman Abbas; Muhammad Umer Faheem; Naeem Ahmed; Atiq ur Rehman; Amer Aziz (Journal of Ayub Medical College Abbottabad, 2025)
Background: Revision as well as primary Arthroplasty with proximal femoral replacement has increased a lot in recent time. Due to increasing surgery rate the complication rate also increases and the main concerning thing in Proximal femur replacement Arthroplasty (PFRA) is rate of dislocation. Hip stability in Arthroplasty is multifactorial like cup position, abductor function capsular repair. In PFRA the dislocation rate is high due to absent or weak abductor function, so cup position plays an important role in reducing dislocation rate in such cases. Methods: This prospective longitudinal study was conducted at department of orthopaedic surgery, Ghurki trust and teaching hospital, Lahore on those patients that had proximal femoral replacement arthroplasty either as primary surgery or revision surgery through standard Hardinge Approach, the cup position in term of Inclination and Ante version was measured postoperatively on x-ray and patient was followed for 12 weeks for any dislocation. Results: Our study comprises of 42 patients with 71.4% were male and 28.6% were female. The mean inclination was 41.23°, ranging from 21–67°, and the mean ante version was 16.43°, ranging from 4–40°. The dislocation rate was 21.42% and the inclination in dislocated patients was 44.05±9.02 and ante version was 17.44±6.42. while the inclination in non-dislocated group is 39.5±10.69 and ante version of 16.43±7.37. Conclusions: Our study concludes that proper cup version and a more horizontal cup inclination plays a major role in preventing dislocation even in the absence of abductors in proximal femoral replacement arthroplasty.